Detection of genes involved in biofilm formation in Staphylococcus aureus isolates - Nourbakhsh, Fahimeh; Namvar, Amirmorteza Ebrahimzadeh (German Medical Science GMS Publishing House, 2016)
is one of the Gram-positive pathogens causing a wide range of nosocomial infections. The present study investigates genotypic and phenotypic aspects involved in biofilm formation in methicillin-resistant strains isolated from nosocomial infections in Isfahan. A total of 110 strains were collected from three major hospitals in Isfahan, the center of Iran. The antibiotic resistance pattern, phenotypes, and biofilm formation genes were studied using Congo red agar (CRA) and multiplex PCR (M-PCR). We found that 103 out of 110 samples (93.6%) were MRSA. The highest frequency of resistance was found to penicillin (89%), ciprofloxacin (87.4%), and erythromycin (86.1%). Phenotypic results showed that 53.5% were high biofilm producers, while 33.3% and 13.2% were intermediate and low biofilm producers, respectively. (69.3%) had the highest frequency in comparison to other intercellular adhesion () genes, (54.8%) was second most common.The results show that the adherence or attachment ability and biofilm production are important for enhancing virulence factors among isolates of strains.